Prince Claus Awards 2001. - Adonis; Afshar, Iraj; Enwezor, Okwui; Hassan, Salah; Koepke, Bruce; Nettleford, Rex; Niehof, Anke; Ortega, Julio; Pastor Roces, Marian; Phan Huy Duong; Pinter, Harold; Prins, Claus; et al. (Den Haag : Prince Claus Fund, 2001)
Stichting Zomercarnaval ; Minshall, Peter ; Abani, Chris ; Duong Thu Huong ; Fosso, Samuel ; Ketab, Jahan-e ; Maftun, Mehri ; Maqdesi, Antoun ; Rivera Mirano, Elena ; Salahi, Ibrahim ; Talingo ; Thays, Ivan
Prince Claus Awards 2001 was presented on 11 December 2001 at the Royal Palace, Amsterdam.
boek